A multidisciplinary model of transitional rehabilitation in acute aged care - Michael, Rene; Wichmann, Helen; Wheeler, B.; Horner, Barbara; Downie, Jill (Australasian Rehabilitation Nurses Association, 2004)
This article describes the first stage of a three-stage pilot research project to establish a Healthy Ageing Unit, in a private hospital in Western Australia, based on a multidisciplinary model of transitional rehabilitation for the elderly acute patient. Results of the Stage One Developmental Needs Assessment and User Consultation indicated the need for post-acute intermediate care for the older patient. An audit of admissions and separations data found that patients aged 65 years and over had an average length of stay of 33.4 days compared with the Australian norm for all patients of 3.7 days and that, in the previous year, more than 322 acute general, medical and surgical patients had been unable to be admitted for treatment because of bed shortages. Moreover, anecdotal information suggested that both nursing staff and patients were frustrated by the lack of time available to adequately provide "enabling" care. The Unit proposed an innovative multidisciplinary model of staffing, with enrolled nurses trained as therapy assistants providing the majority of care. The development of selection criteria for the Unit was based on data identified from medical records and focus groups. Medically stable acute patients aged 60 years and over were referred to the Unit and were assessed as suitable candidates for therapeutic nursing if they had the expected ability to improve/rehabilitate within a two-week time frame. Patients who were assessed as unable to make this progression were deemed unsuitable candidates and admitted to the conventional care wards for other support and discharge planning.